Japanese and Oriental ceramics - Gorham, Hazel H. (Charles E. Tuttle Company, 1971)
Contents: Japanese and Oriental Ceramics was first published in print form by Tuttle Publishing in 1971. This comprehensive and profusely illustrated work tells how to distinguish Japanese porcelains from Chinese, and how to recognize modern reproductions of genuine old wares. It is completely indexed, contains a lengthy bibliography, and lists Chinese dates important in any discussion of Oriental ceramics. Crammed with information on the history, esthetics, and technical aspects of the ceramics of Japan and the Orient, the book is an invaluable guide to scholars, collectors and dealers.